Polynoe caeciliae Fauvel (Polynoidae), ein mit Korallen assoziierter Polychaet. - Hartmann-Schröder, Gesa (Mitteilungen aus dem Hamburgischen zoologischen Museum und Institut, 1985)
Polynoe caeciliae FAUVEL, 1913 (Polynoidae, Harmothoinae) known only from its original discovery (off Portugal Islands of Cape Verde) will be redescribed from the type material. The species is associated with corals probably as a commensal. Recent studies of coral samples from different places within the Lusitanian Region result in new findings of Polynoe caeciliae. Two other findings are from the Indian Ocean (Komore Islands). A comparison with specimens of both areas does not show any morphological differences.
World Polychaeta Database (WPolyD).